[OP.6A.06] VASCULAR PHENOTYPES BY ASSESSING PERIPHERAL AND CENTRAL BLOOD PRESSURE IN OBESE YOUTH. (September 2016) - LURBE, E.; Torro, M.I.; Alvarez-Pitti, J.; Redon, P.; Redon, J.
Abstract : Objective: To identify vascular phenotypes across BP conditions in overweight and obese youths, by assessing office (oBP) and central BP (cBP), and pulse pressure amplification. Whether or not 24-hour ambulatory BP monitoring and pulse wave velocity (PWV) add insight to the issue has also been examined. Design and method: White youths of both sexes with overweight or obesity and of European origin, ranging from 8 to 18 years of age, were included. Office BP, cBP, PWV, and 24-hour ABPM were measured. Office BP conditions and "white-coat" HTN were defined as recommend by ESH Guidelines in Children and Adolescents. Subjects were divided into subgroups of "normal" or "high" according to cBP and PP ratio. Results: A total of 593 subjects (mean age, 12.2 ± 2.3 years; 275 females) were included in the study. The largest differences between oSBP and cSBP correspond to the isolated systolic HTN (ISH) group, in which only 25% of subjects have high cBP, in contrast to 50% of the systo-diastolic HTN (SDH) group. In the hypertensive youth two patterns emerged based on cBP and PP ratio. The highest cBP was among the SDH and the highest PP ratio in the ISH group (see Figure). While, 90% of the SDH were confirmed with 24-hour ABPM, 75% of the ISH were white-coat. PWV showed a progressive increment across the groups from NT to SDH. Significant differences were observed only when compared to the NT, but not among all other groups. Figure. No caption available. Conclusions: In overweight and obese hypertensives, ISH is prevalent posing a challenge for the clinician of whether these may therefore be diagnosed and managed as hypertensives. Until prospective studies can give more information, 24-hour ABPM can offer information for making clinical decisions.